Rancang Bangun Pengendali Perangkat Elektrik Rumah Menggunakan Fuzzy Logic Berbasis Raspberry Pi dan Web - Eko Nugroho Lestariawan (Jurnal Jaringan Telekomunikasi, 2018)
Conventional access control systems such as manual light switches are now being developed with electric light switches that can be controlled remotely using a web. Raspberry Pi is one of the newest technologies, namely a mini computer that can be used in an automatic access control system. This technology can be applied using one of the sciences of artificial intelligence, namely fuzzy logic control. Fuzzy logic is an appropriate way to map an input space into an output space. In this final project research is designed a home electric device control system using fuzzy logic based on Raspberry Pi and Web. The Arduino nano is also used in the system as a fuzzy lamp controller. To be able to control via the Raspberry Pi, an ip is needed for communication between the web and raspberry, namely 192.168.1.204. From the test results on the lamp, the light intensity and lamp voltage change based on the light sensor input, the voltage of 10 volts of the lamp produces 10 lux of light intensity, 60 volts = 51 lux and 220 volts = 320 lux while for the fan the speed is directly proportional to the amount of temperature. When the temperature is set to 28 oC and the sensor reads a temperature of 28.25 oC the PWM output of the fan = 95 and when the temperature is 34 oC the output is 40. The greater the PWM output, the slower the fan rotation.